ANALISIS PERHITUNGAN PENYUSUTAN ASET TETAP MENURUT STANDAR AKUNTANSI KEUANGAN PADA BENGKEL TOGAR - Nikijuluw, Henny; Hariyanti, Dwi; Syauta, Gracia (ISAS, 2023)
The purpose of writing is to determine the depreciation value of fixed assets according to Financial Accounting Standards at Togar Workshop. The analytical method used is quantitative descriptive analysis, namely calculating the depreciation value on fixed assets in the business.The research results show that building fixed assets experience accumulated depreciation based on their useful life of 20 years amounting to IDR 1,500,000,- with a purchase price of IDR 30,000,000,-. Machinery fixed assets experience accumulated depreciation based on their useful life of 7 years amounting to IDR 1,164,286,- with a cost of IDR 8,900,000,-. Furthermore, vehicle fixed assets experience accumulated depreciation based on their useful life of 10 years amounting to IDR 2,000,000.- with a purchase price of IDR 20,000,000,-. Then the fixed assets of workshop equipment experience accumulated depreciation based on their useful life of 5 years amounting to IDR 2,100,000,- with a purchase price of IDR 12,000,000,-. Keywords: Depreciation, Fixed assets